Information Seeking Behavior Patterns of SMKN 1 Medan Students Regarding Contemporary Idols - Inggrid Masita Dewi*; Franindya Purwaningtyas (Universitas Syiah Kuala, 2023)
This study discusses the information-seeking behavior patterns of SMKN 1 Medan students regarding contemporary idols. The research aims to understand how the information-seeking behavior patterns of SMKN 1 Medan students unfold in the context of contemporary idols. The research employs a qualitative approach with a case study design. Data collection techniques include interviews, observations, and documentation. The findings reveal that SMKN 1 Medan students exhibit unique patterns when seeking information about contemporary idols, although there are some similarities with the Information Search Process theory previously proposed by Khultau. These patterns begin with problem recognition and the identification of information needs, followed by selecting a search system, formulating queries/keywords, conducting in-depth searches, filtering acquired information, and finally presenting the information. This outlines the information-seeking behavior patterns of SMKN 1 Medan students concerning contemporary idols.